2017
DOI: 10.1002/ddr.21383
|View full text |Cite
|
Sign up to set email alerts
|

Anti‐Inflammatory Effects of PEGylated Human Adrenomedullin in a Mouse DSS‐Induced Colitis Model

Abstract: Preclinical Research Human adrenomedullin (hAM), a hypotensive peptide, also has anti-inflammatory effects. hAM can reduce the severity of the dextran sulphate sodium (DSS)- and 2,4,6-trinitrobenzene sulfonic acid (TNBS)-induced colitis in animal models. Furthermore, in a clinical study, hAM treatment reduced the Disease Activity Index in ulcerative colitis. However, these therapeutic effects required continuous administration of hAM as the half-life of native hAM is quite short in blood. To resolve this probl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 27 publications
(32 reference statements)
1
20
0
Order By: Relevance
“…3, C and F), it seems likely that the disulfide does in fact impart a significant affinity increase. The ability to incorporate a disulfide bond into AM2/IMD could be valuable for therapeutic development because it might increase peptide stability in plasma, which is an important consideration for these peptides (54,55).…”
Section: Receptor-bound Adrenomedullin 2/intermedin Conformationmentioning
confidence: 99%
“…3, C and F), it seems likely that the disulfide does in fact impart a significant affinity increase. The ability to incorporate a disulfide bond into AM2/IMD could be valuable for therapeutic development because it might increase peptide stability in plasma, which is an important consideration for these peptides (54,55).…”
Section: Receptor-bound Adrenomedullin 2/intermedin Conformationmentioning
confidence: 99%
“…It will be interesting to see which cell type plays a more important role. It is clear that a mixed acute and chronic inflammatory reaction takes place in H. pylori-induced inflammatory environments, where multifarious immune cell types infiltrate and play complicated roles 16,17,51,52 . In a recent report, TLR9 −/− mice were found to show increased signs of gastritis upon H. pylori infection 53 .…”
Section: Discussionmentioning
confidence: 99%
“…For example, it has been reported that overexpression of ADM in the stomach can inhibit gastric acid secretion 14 . In other studies, ADM protects the mucosa as an endothelial cell growth factor by promoting mucosal healing 15 , and has antiinflammatory effects in a mouse DSS-induced colitis model 16 . However, the relationship between ADM and gastric inflammation, especially in H. pylori-associated gastritis, is presently unknown.…”
Section: Introductionmentioning
confidence: 90%
“…For example, it has been reported that over-expression of ADM in the stomach can inhibit gastric acid secretion [11]. In other studies, ADM can protect mucosal as an endothelial cell growth factor by promoting mucosal healing [12], and has anti-inflammatory effects in a mouse DSS-induced colitis model [13]. However, the relationship between ADM and gastric inflammation especially in H. pylori -associated gastritis is presently unknown.…”
Section: Introductionmentioning
confidence: 99%